Translation Analysis in Sentence Patterns Found in the “Good Earth” - Juliarta, I Made (e-Journal of Linguistics, 2023)
This study aims to: (i) analyze the tree diagram structure of sentence patterns found in the novel “The Good Earth”, (ii) analyze the types of translation shifts in sentence patterns in the translation process that were found in the data source. The novel entitled “The Good Earth” is a famous literary work that was written by Pearl S. Buck. It told about family life in a village in China before the world war I. This novel was the best seller at that time. This research focuses on The Syntax Analysis and Its Translation Found on Sentence Patterns in the story from novel entitled “The Good earth”. This study also focuses on analyzing the tree diagram structure and the types of translation shifts in translating from the source language into target language. The analysis applied the theory of sentence patterns that was proposed by Quirk and Greenbaum and the theory of translations shift proposed by Catford. The process of collecting data was started by reading the novel in order to understand the novel entitled “The Good Earth” and observe the data of sentence patterns that could be taken from the data source. In the method of collecting data, the novel was read in order to find out data of complex sentences and simple sentence that were found in the novel. The research study found that there were seven sentence patterns that were translated by applying unit shift and translation shift. The data were analyzed based on syntax analysis, types of sentences, sentence pattern, tree diagram, and relevant previous studies.